Viljelijöiden eläketurvan taloudellinen tarkastelu - Rantamäki-Lahtinen, Leena (Maatalouden taloudelllinen tutkimuslaitos, 1999)
1990-luvun lamavuosina MYEL-maksuja on jouduttu korottamaan ja viljelijöiden eläke-etuuksia heikentämään valtiontaloudellisista syistä. MMM Leena Rantamäki-Lahtisen tekemässä tutkimuksessa selvitettiin suomalaisen viljelijän eläketurvan tasoa ja sitä, mitä voimassa oleva eläketurva hänelle maksaa. Tutkimuksessa tarkasteltiin viljelijän eläketurvan ja eläkemaksujen tasoa verrattuna tilalta saatuihin tuloihin. Tulojen vertailu perustuu kirjanpitotiloista tuotantosuunnittain muodostettuihin tilamalleihin. Lisäksi tutkimuksessa tarkasteltiin nykyarvomenetelmän avulla eri suuruisten MYEL-työtulotasojen mukaisten eläkemaksujen ja kokonaiseläkkeiden välisiä suhteita sekä verrattiin lakisääteisen eläkevakuutuksen kustannuksia vastaavaan yksilölliseen eläkevakuutukseen. MYEL-työtulotaso vaikutti siihen, kuinka hyvin laskennallinen MYEL-työtulo ja tilasta saadut tulot vastasivat toisiaan. Viljatilalla saadut tulot ylsivät vain puoleen MYEL-normaalityötulosta, sikatilalla tulot jäivät hieman MYEL-työtuloputken alalaidan alle ja maitotilalla tilasta saadut tulot vastasivat normaalityötuloa. Maksujen ja kokonaiseläkkeiden välinen suhde oli viljelijälle edullisin alimmilla MYEL-työtulotasoilla, sitä vastoin maksujen ja kokonaiseläkkeiden välisen erotuksen nykyarvot olivat suurimmat korkeammilla työtulotasoilla. Tutkimuksen perusteella voidaan todeta, että viljelijöiden eläkeiän tulotaso on turvattu ja riittävä verrattuna nykyiseen tulotasoon. Mikäli viljelijä haluaa kasvattaa saamaansa eläkettä, yksilöllinen eläkevakuutus on kuitenkin edullisempi vaihtoehto kuin lakisääteinen eläkevakuutus. Viljelijän kannattaa maksaa työtuloputken alalaidan mukaisia eläkemaksuja ja hankkia korkeampien MYEL-työtulojen mukainen eläketurva yksilöllisellä eläkevakuutuksella.

Finland has a public pension program that is divided into two separate parts. The first part consists of earnings-related pensions, in which people contribute to the system during their working life in exchange of earnings-related benefits after retirement. The second part consists of basic pensions for all Finnish citizens. The amount of basic pension depends on the amount of earnings-related pension, basic pension reduces as earnings-related pension increases. Farmers have their own earnings-related pension program, where they pay fees during their active farming years and receive benefits after retirement. This study analyses economic prospects of farmers retirement program (MYEL) in Finland under alternative payment schemes and retirement ages. The study has two major goals. The first is to find out how much farmers income will change after retirement and how much retirement plan will cost them compared to its expected benefits. The second is to figure out how competitive the public retirement plan is compared to a private insurance that can be, within certain limits, substituted for the public program. The comparison is made from the farmer s perspective. Expected benefits and losses of the alternative retirement slays were compared using the representative farm approach. The representative farm was defined for three different farms: dairy farm, hog farm and grain farm. These farms were computed from the results 1995 of bookkeeping farms in Southern-Finland. In the first part farmer s labour income was compared to his/her MYEL-income. The expected present value of the earnings-related insurance fees was compared to the expected present value of pensions (both earnings-related and basic pensions combined). The present value technique was also used for the comparison between the private pensions and public programs. The MYEL income is a computational income defined by farmers pension program. It is based on the farms arable land and forest area. Farmers can quite freely define the MYEL income of their farms within certain limits. The MYEL income influences the fees and later to the amount of the earnings-related pension. On the other hand, the production line has great effect on the farm s labour income. Hence, the possible fall in farmer s income is largely determined by the individual choice of the MYEL income level. For this reason three different MYEL income levels were defined for each different representative farm. These MYEL income levels were the lowest possible one, "normal" and the highest possible one. On the dairy farm the "normal" on-farm MYEL income was equal to labour income. On the hog farm the lowest MYEL income was higher than labour income, but the discrepancy was not substantial. On the farm, that produced grain only the normal MYEL income was twice as large as on-farm labour income. Therefore, as the monthly amount of pension depends on the MYEL income, the farmer s standard of living does not fall significantly after retirement. The discount rate and MYEL income level affects the relative value of the fees and expected values of pensions. As expected, increasing discount rate reduces significantly the expected Net Present Value (NPV) of the pension scheme. The discount rate on which the NPV will turn negative depends on the MYEL-income level: on the higher level it will turn to negative at lower interest rates. In the basic-model, where it was assumed that farmer pays fees for 37 years, retires at the age of 65 and expected NPV of pensions is calculated until the age of 88, the NPV turned negative at interest rates from 4 to 9 %. In the basic-model the farmer was entitled for full earnings-related pension (60 % of the active-time s income). The significance of not achieving the full earnings-related pension was measured by the sensitivity analysis. The result of the analysis was that increased basic pension compensated quite well for the deficiency of full earnings-related pension: the amount of pension fell only from 2 to 12 %, (pensions were from 45 to 55 % of the active time s income). The results suggest that the most beneficial method to gain pension which is equal to pension received from normal or the highest possible MYEL income is to combine the public and private programs. Thus, the largest expected NPV can be achieved by purchasing the lowest possible insurance level through the public program and then increasing the pension by the private insurance.
Julkaisussa abstraktissa väärä vuosiluku
Keywords: Ma; tulot; eläkkeet; nykyarvo; eläkejärjestelmät; income; pension; present value; retiment program